PROFILE OF HIGH SCHOOL STUDENTS’ ENVIRONMENTAL CARE TROUGH BIOLOGY LEARNING - Widya Arwita; Aulia Sari Nuriza (ATRIUM PENDIDIKAN BIOLOGI, 2021)
This study aims to determine the environmental care of students in SMA Negeri 13 Medan. Population of the research is student of X MIA SMA Negeri 13, and the samples used is X MIA 1, X MIA 2, X MIA 3 and X MIA 4, which taken by purposive sampling. The data was conducted via Google forms. This research is a descriptive type through a survey using questionnaire instruments. The results of this study are students with the very high category was 35%, the students in the high category were 63%, the students in the medium category had the percentage of 2%, and the students in the low and very low category were 0%. The conclusion of this study is environmental care attitude of X MIA SMA 13 Medan students on Ecosystem topic was in the high category.